PTH-140 Dual modality endoscopic therapy for barrett's-associated oesophageal dysplasia in a tertiary referral centre: completing the audit cycle. (22nd June 2015) - Almond, M; Florance, C; Old, O; Oliphant, ZC; Barr, H
Abstract : Introduction: The efficacy of dual modality endotherapy with endoscopic resection and mucosal ablation is now well documented in the treatment of Barrett's-associated early neoplasia. This strategy was supported by a consensus survey of international experts in 2011 with the aim of achieving high rates of complete eradication of dysplasia and intestinal metaplasia (CE-D and CE-IM). 1 This re-audit of clinical practice in a single tertiary oesophagogastric unit aimed to assess whether patients with Barrett's-associated early neoplasia received dual modality endoscopic therapy in order to achieve CE-D and CE-IM. Method: In 2011 an audit standard was defined recommending that patients with early glandular neoplasia (high-grade dysplasia (HGD) +/- intramucosal cancer (IMC)) should receive dual modality endoscopic therapy aiming for CE-IM. In the initial audit phase a prospectively maintained database was interrogated between 2004–2011 in order to assess current practice. Changes in practice were implemented following in-house presentation to the oesophagogastric MDT in 2011, and practice and outcomes between 2012–2014 were re-audited. Results: The initial audit included 72 patients with a median follow-up of 38 months treated by ER +/- ablative therapy with curative intent for HGD (88%) or IMC (12%). The re-audit included 43 patients: LGD 2 (5%), HGD 31 (72%) and IMC 10 (23%), with a median follow-up was 21 months. The use of ablation therapy post-ER was higher in the re-audit group (86% vs 60%; p = 0.003). Rates of CE-D and CE-IM were also higher in the re-audit group (79% vs. 29%; p < 0.001) and (28% vs. 1%; p < 0.001) respectively. Disease progression to invasive cancer (at least T1b) appeared lower in the re-audit group although did not achieve statistical significance (2% Vs. 11%; p = 0.150). Conclusion: This completed audit cycle demonstrated that use of dual modality endoscopic therapy has increased since 2011. This was associated with higher CE-IM and CE-D rates. Regular audit and re-audit can improve outcomes in patients receiving endoscopic therapy for early Barrett's-associated neoplasia. Disclosure of interest: None Declared. Reference: Bennett C, Vakil N, Bergman J, et al . Consensus statements for management of Barrett's dysplasia and early-stage esophageal adenocarcinoma, based on a Delphi process. Gastroenterology. 2012;143(2):336–46